Sublethal Injuries and Physical Abnormalities in Maldives Manta Rays, Mobula alfredi and Mobula birostris - Strike, Elspeth M.; Harris, Joanna L.; Ballard, Kirsty L.; Hawkins, Julie P.; Crockett, Jennifer; Stevens, Guy M. W. (Frontiers in Marine Science, 2022)
Manta rays in the Maldives are not directly exploited by fisheries, but they still sustain sublethal injuries from entanglement in fishing lines, ropes, and nets, and from boat strikes. Sublethal injuries and physical abnormalities also occur naturally from predation events, deformity, parasites, and disease. To determine the type and frequency of anthropogenic and natural originated injury events affecting Mobula alfredi and M. birostris, we examined data from the Manta Trust’s Maldivian Manta Ray Project (MMRP) database, which contains 72912 photo-identification (photo-ID) sightings of the two manta ray species from 1987 – 2019. The likely origin of each injury or physical abnormality was determined based on visual assessment of the photo-ID images. Multiple injuries to an individual originating from the same event were grouped for analysis. Generalised linear mixed models (GLMM) were used to investigate the relationship between the occurrence of injury events and the explanatory variables sex and maturity status for both species, with the additional variable site function (cleaning, feeding, cruising) investigated for M. alfredi. Spatial and temporal variations in M. alfredi injury events, and their origin and type, were investigated by calculating the percentage of injury events per sighted individual at each Maldivian atoll, and per re-sighted individual in each year from 2005  2019. For both manta ray species, injury events were predominantly of natural origin, with predatory bites being the most frequent type. The most common anthropogenic injury type was entanglement in fishing line. Injuries to M. alfredi were significantly more likely to be observed on juveniles than adults, males than females, and at cleaning stations as opposed to feeding or cruising sites. Neither sex nor maturity status were significant explanatory variables for the occurrence of injuries to M. birostris. Highest percentages of anthropogenic injuries per sighted M. alfredi were recorded in North Malé, South Malé, Baa, Addu, and Laamu Atolls, where boat traffic, fishing, and tourism activities are concentrated. Overall, this work greatly improves understanding of the sublethal threats faced by manta rays in the Maldives; identifying focus areas where conservation management actions are required to ensure more effective protection of this threatened species group.